2016
DOI: 10.1523/jneurosci.3131-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Glycolysis in the Frontal Cortex Correlates with Memory Performance in Wild-Type Mice But Not the APP/PS1 Mouse Model of Cerebral Amyloidosis

Abstract: Aerobic glycolysis and lactate production in the brain plays a key role in memory, yet the role of this metabolism in the cognitive decline associated with Alzheimer's disease (AD) remains poorly understood. Here we examined the relationship between cerebral lactate levels and memory performance in an APP/PS1 mouse model of AD, which progressively accumulates amyloid-␤. In vivo 1 H-magnetic resonance spectroscopy revealed an age-dependent decline in lactate levels within the frontal cortex of control mice, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 27 publications
8
61
0
Order By: Relevance
“…This corroborates the recent finding of elevated MRS‐measured lactate in transgenic AD mice compared to wild‐type mice, in which it is associated with memory deficits 56. Whereas older MRS studies failed to show any discernable lactate differences in AD,57, 58 our finding and that of a recent study54 align with this very strong mechanistic data 55, 56. Despite the biological plausibility of the finding, we interpret our results on Lac with caution as quantitation of Lac can be affected by signals from macromolecules which partially overlap with the Lac signal in the J‐PRESS spectrum 24…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This corroborates the recent finding of elevated MRS‐measured lactate in transgenic AD mice compared to wild‐type mice, in which it is associated with memory deficits 56. Whereas older MRS studies failed to show any discernable lactate differences in AD,57, 58 our finding and that of a recent study54 align with this very strong mechanistic data 55, 56. Despite the biological plausibility of the finding, we interpret our results on Lac with caution as quantitation of Lac can be affected by signals from macromolecules which partially overlap with the Lac signal in the J‐PRESS spectrum 24…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we found an elevation in lactate in AD compared to control subjects, which also survived the correction made for CSF volume. This corroborates the recent finding of elevated MRS‐measured lactate in transgenic AD mice compared to wild‐type mice, in which it is associated with memory deficits 56. Whereas older MRS studies failed to show any discernable lactate differences in AD,57, 58 our finding and that of a recent study54 align with this very strong mechanistic data 55, 56.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We previously saw an exaggerated response in ISF A␤ to hyperglycemia in aged mice with significant amyloid pathology (Macauley et al, 2015). Here, we report new found differences at baseline in blood and ISF glucose between young and aged APP/PS1 mice that correspond with changes in lactate that we previously reported (Harris et al, 2016). Conversely, there was no baseline difference in blood insulin levels, which may explain why we saw an exaggerated response to hyperglycemia in aged mice but a similar response to insulin.…”
Section: Discussionsupporting
confidence: 86%
“…4 A, B). Previously, we reported that baseline hippocampal ISF lactate levels were significantly increased in 12-month-old APP/PS1 mice compared with 3-monthold APP/PS1 mice (Harris et al, 2016). Here, we found that fasted blood glucose as well as hippocampal ISF glucose were lower in 12-month-old compared with 3-month-old APP/PS1 mice (blood: p Ͻ 0.001, t ϭ 4.1, 129.0 Ϯ 5 vs 95.9 Ϯ 6.5 mg/dl; ISF: p Ͻ 0.01, t ϭ 2.5, 0.20 Ϯ 0.01 vs 0.15 Ϯ 0.01 mM) (Fig.…”
Section: Resultsmentioning
confidence: 87%